PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS MODEL DISCOVERY LEARNING PADA MATERI BARISAN BILANGAN DI KELAS VIII SMP - Afriza, Yosep Yendra; Hutapea, Nahor Murani; Armis, Armis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to produce mathematics learning devices in form of syllabus, Lesson Plan (LP), and Student Worksheet (SW) based on discovery learning on number sequence material in eigth grade. Development model used is 4D that consist of define, design, develop, and dissemination. The research is limited to develop stage. Testing conducted included validity test on syllabus, four LP, and four SW, along with practicality test of the SW usage. Validty test was conducted by involving two experts and a practitioner, then practicality test was conducted in small-group test at SMPN1 Tualang by involving ten students. Validity Data included scores and validator’s suggestions that collected with questionnare technique used validator sheet. Practicality Data included scores and respondent’s suggestion that collected with questionnare technique used students response questionnare. The suggestions collected was analyzed with data reduction method, and the scores collected was analyzed with editing, coding, and data tabulation method. In data tabulation, calculations are performed to determine average percentage scores of the validation and small group test results. Based on the data analysis of the validation results, obtained the average percentage score for: (1) syllabus 94,81%; (2) LP overall more than 94%; and (3) SW overall more than 91%, then based on the data analysis from the result of questionnaire of students response, obtained the average percentage score for SW overall more than 87%. Thus, it can be concluded also that the learning devices have complied very valid criteria, and the SW also has complied very practical criteria.Keyword: Mathematic Learning Devices, Discovery Learning, Development Research,4D Model